همزتا القطع والوصل في سورة النساء (الآية 1-50) - Cindy Pratiwi Putri (Jurnal Dirosah Islamiyah, 2023)
This research aims to determine the number of Hamzah Qath'i who are located above _alif_ (أ), above _ya'_ (ئ), and above _waw_ (ؤ), as well as the number of Hamzah Washl in Surah An-Nisa'. This is qualitative research with an analytical nature. Data collection was carried out by searching for verses in Surah An-Nisa' that contain Hamzah Qath'i and Hamzah Washl. These verses were then collected, followed by reading books related to the discussion of Hamzah Qath'i and Hamzah Washl, and the last one was to analyze both. The research results obtained in Surah An-Nisa's verses 1–50 show that the number of Hamzah Qath'i located above the _alif_ is 225, the number of Hamzah Qath'i located above the _ya'_ is 40, the number of Hamzah Qath'i located above the _waw_ is as many as 225, and the number of Hamzah Washl is as many as 213.